2016
DOI: 10.18512/1980-6477/rbms.v15n3p461-469
|View full text |Cite
|
Sign up to set email alerts
|

CARACTERÍSTICAS CULTURAIS E PATOLÓGICAS DE Bipolaris maydis EM DIFERENTES MEIOS DE CULTURA

Abstract: CARACTERÍSTICAS CULTURAIS E PATOLÓGICAS DE Bipolaris maydis EM DIFERENTES MEIOS DE CULTURA Ribeiro, julianasaltiresdossantos@yahoo.com.br, amaraljr@pq.cnpq.br, mrclvivas@hotmail.com, janielims19@yahoo.com.br, railanferreira@hotmail.com, silvaldo@uenf.br Revista Brasileira de Milho e Sorgo, v.15, n.3, p. 462-470, 2016 RESUMO A mancha de Bipolaris, causada por Bipolaris maydis, é uma das principais doenças foliares de Zea mays, apresentando um considerável potencial de dano, notadamente, na cultura do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…Images captured under a microscope allowed us to detect the pseudo‐septate structure of asexual spores produced by the phytopathogenic fungus Bipolaris maydis . Previous studies found a similar coloration and pseudo‐septate conidia (Pal et al, 2015; Santos et al, 2016). Based on colour in the colony, in their study, Ferreira et al (2022) found the predominance of the colony texture being cotton wool, with grey‐ dark greenish in the front and black colour at the colony back, during B. maydis identification.…”
Section: Resultssupporting
confidence: 73%
“…Images captured under a microscope allowed us to detect the pseudo‐septate structure of asexual spores produced by the phytopathogenic fungus Bipolaris maydis . Previous studies found a similar coloration and pseudo‐septate conidia (Pal et al, 2015; Santos et al, 2016). Based on colour in the colony, in their study, Ferreira et al (2022) found the predominance of the colony texture being cotton wool, with grey‐ dark greenish in the front and black colour at the colony back, during B. maydis identification.…”
Section: Resultssupporting
confidence: 73%